STOCK PRICE DETERMINANTS: BEFORE AND DURING THE COVID-19 PANDEMIC - Ardila, Lina Nur; Saputra, Dany Adi; Budiwati, Christiyaningsih; Syafiqurrahman, Muhammad (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to analyze the effect of financial variables, namely Earnings per Share (EPS), Return on Assets (ROA), Debt to Equity Ratio (DER), and Price to Book Value (PBV) on Stock Prices in companies listed on the Indonesia Stock Exchange during the period 2018-2021. The analysis method used is multiple linear regression to test the effect of each variable partially and simultaneously. The results of the study show that in 2018-2019, EPS, ROA, and PBV have a significant effect on Stock Prices, while DER does not have a significant effect. Conversely, in 2020-2021, only EPS shows a significant effect on Stock Prices, while ROA, DER, and PBV do not have a significant effect. The overall regression model shows good ability in explaining variations in Stock Prices, with high R Square values, namely 78.7% for 2018-2019 and 82.4% for 2020-2021. This research is expected to provide insight for investors in making investment decisions based on the company's financial performance.